Pengaruh Green Accounting, Carbon Emission Disclosure, dan Profitabilitas terhadap Nilai Perusahaan - Fina, Fina (Department of Accounting, Faculty of Economics & Business, 2024)
The value of a company becomes the primary measure of performance to understand how a company is valued and appreciated in a business environment. However, rapid economic growth has led to increased environmental problems. The solution to this is to invest in environmental rehabilitation programmes to gain legitimacy in the public eye and the availability of information that can be a signal about the company's strategy especially in terms of environmental and social aspects. The study aims to analyze the impact of green accounting, carbon emission disclosure, and profitability on the value of companies in the mining sector listed on the Indonesian Stock Exchange period 2021-2023. Sampling techniques are purposive sampling with samples of 32 companies. Quantitative approaches of causal associative types, data analysis involves descriptive statistical tests, classical assumption tests, and double linear regression. The results show that green accounting and carbon emission disclosure have no significant impact on the value of a company, while profitability has a significant impact. Although green accounting and carbon emission disclosure are expected to enhance the corporate image through environmental responsibility, these findings suggest that markets and investors have not fully appreciated this information in their assessment. Profitability, as an indicator of financial performance, has proven to be a major factor that increases the value of a company.